APPLICATION OF SCHRYVER REAGENT FOR ANALYSIS OF FORMALDEHYDE IN ALCOHOLIC BEVERAGES - Suryanto, Andri
Formaldehyde is a toxic compound with Tolerable daily intake (TDI) of 0.2 mg/kg BW/day or equivalent to 12 mg/person/day when the body weight is assumed to be 60 kg. This compound may be found in alcoholic beverages as chemical contaminant with tolerable concentration (TC) of 2.6 mg/L according to WHO. In frame work of formaldehyde exposure assessment in this product, an analytical method is needed for identification and quantification of this compound. The aim of this research was to obtain an analytical method applicable for routine analysis of formaldehyde in alcoholic beverages by means of Schryver method. Formaldehyde reacts with Schryver reagent to form a derivative absorbs radiation in visible region. Schryver reagent was prepared according to reported method. Standard stock solutions and working standard solutions of formaldehyde were prepared from a standardized concentrated formaldehyde solution. To determine the wave length with maximum absorption, visible absorption spectrum of analyte was measured in the range of 400 to 800 nm. Following spectrum measurement, stability of absorbance was measured at maximum wave length for 60 minutes. For qualitative analysis purposes, formaldehyde working standard solutions with end concentrations in the range of 1 to 12 ppm as well as two alcoholic beverage samples with and without formaldehyde spiking were reacted with Schryver reagent and the color formation was observed then qualitative limit of detection was determined. A calibration curve was plotted between formaldehyde working standard solutions with end concentrations in the range of 2 to 10 ppm versus absorbance of these solutions. The visible absorption spectrum of analyte shows a maximum wavelength at 519 nm and the absorbance was relatively stable for 60 minutes. The qualitative test revealed that the limit of detection of formaldehyde was 1 ppm. Formaldehyde was detected in one sample but due to color interferences was failed to be detected in the second sample. Measurements of formaldehyde v working standard solutions for plotting of calibration curve revealed that the absorbance values were not reproducible and hence could not be farther applied for quantitative analysis. Based on overall results, it was concluded that the Schryver reagent under experimental conditions could be applied for qualitative analysis of formaldehyde in alcoholic beverages.